Pengaruh Kebutuhan Aktualisasi Diri terhadap Potensi Bakat Siswa SMA Negeri 2 Kota Bengkulu - Ariani, Winda Ade; Kurniah, Reni; Jannah, Nurul (Attractive : Innovative Education Journal, 2022)
The problem that is often faced by students is the problem of finding the potential talent that exists in them. In addition, the process of self-actualization that is not easy makes it difficult for teenagers to experience it. Talent is an innate ability that is more or superior which is a potential that still needs to be trained and developed. Self-actualization is the tendency to realize and develop the talents, capacities, and abilities of a human being. Academic self-actualization is self-actualization in the academic or educational field. This study aims to determine the effect of self-actualization on the talent potential of SMA Negeri 2 Bengkulu City students. The object of this research is the students of class X and XI science, totaling 100 people. The research variable consists of two variables, namely the independent variable is self-actualization and the dependent variable is the potential talent of students. The data collection method used is a Likert scale questionnaire. The data analysis method used is a simple linear regression analysis method. The results showed that the average level of student self-actualization was included in the very high category, this can be seen from the number of students who fall into that category as much as 65%. Based on the results of the study, there is a significant influence on the need for self-actualization on the potential talents of SMA Negeri 2 Bengkulu City students.